2005
DOI: 10.1002/ajmg.1320370616
|View full text |Cite
|
Sign up to set email alerts
|

Williams syndrome: An historical perspective of its evolution, natural history, and etiology

Abstract: This review examines the Williams syndrome (WS) from an historical perspective, beginning with the early descriptions of idiopathic infantile hypercalcemia (IIH) and ending with some speculative ideas about a possible causative function of a recently discovered neuropeptide. The earliest reports of W S individuals are probably those which describe a "severe" subgroup of IIH and separate it from the epidemic of milder IIH reported in Post-WWII Great Britain and Europe. Most of these latter cases apparently resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 70 publications
0
11
0
1
Order By: Relevance
“…The most commonly reported endocrine abnormality in WBS is infantile hypercalcemia [Morris et al, 1988;Jones, 1990]. The incidence of hypercalcemia was estimated to be about 15%.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported endocrine abnormality in WBS is infantile hypercalcemia [Morris et al, 1988;Jones, 1990]. The incidence of hypercalcemia was estimated to be about 15%.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly discussed endocrine abnormality in WS is hypercalcemia, with most reports focusing on infantile hypercalcemia [Jones, 1990]. Despite the attention paid to this complication, the incidence of hypercalcemia is at best imprecisely estimated at 15% [2001] and the etiology and natural history continue to be unknown.…”
Section: Discussion Of Endocrine Findingsmentioning
confidence: 99%
“…1 The causes of hypercalcaemia in WBS are unknown; however, the proposed mechanisms causing hypercalcaemia include vitamin D sensitivity, increased 1,25 dihydroxyvitamin D levels, and defective calcitonin synthesis or release. 1,6,7 Despite the multiple endocrine, cardiovascular, and gastroenterologic problems reported in these patients, studies looking at metabolism and bone quality are virtually absent from the literature. In a small clinical study conducted on 20 WBS adults of at least 30 years of age, the authors reported 12 individuals meeting criteria for either osteoporosis or osteopoenia at the femoral site, and 10 individuals meeting criteria for either osteoporosis or osteopoenia at the lumbar site.…”
Section: Introductionmentioning
confidence: 99%